2012
DOI: 10.1093/aje/kwr464
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Arsenic Exposure From Drinking Water and Plasma Levels of Cardiovascular Markers

Abstract: The authors conducted a cross-sectional study to assess the relation between arsenic exposure from drinking water and plasma levels of markers of systemic inflammation and endothelial dysfunction (matrix metalloproteinase-9, myeloperoxidase, plasminogen activator inhibitor-1, soluble E-selectin, soluble intercellular adhesion molecule-1 (ICAM-1), and soluble vascular adhesion molecule-1 (VCAM-1)) using baseline data from 668 participants (age, >30 years) in the Health Effects of Arsenic Longitudinal Study in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 68 publications
2
63
2
2
Order By: Relevance
“…In a cross-sectional analysis of 115 adults (20–65 years of age) with arsenic-related skin lesions from Araihazar, Bangladesh, there was a positive association of arsenic exposure at moderate levels (range 3–864 μg/L), measured as both well-water arsenic and total urinary arsenic, with plasma levels of sICAM-1 and sVCAM-1 [70]. The same group subsequently conducted independent separate cross-sectional analyses and confirmed a positive association between lower arsenic exposure (median 23 μg/L, range 0.1–500.6 μg/L) and plasma levels of sVCAM-1 [71]. However, no significant association was observed for plasma levels of sE-selectin and sICAM-1.…”
Section: Markers Of Endothelial Dysfunction Inflammation and Oxidatmentioning
confidence: 97%
“…In a cross-sectional analysis of 115 adults (20–65 years of age) with arsenic-related skin lesions from Araihazar, Bangladesh, there was a positive association of arsenic exposure at moderate levels (range 3–864 μg/L), measured as both well-water arsenic and total urinary arsenic, with plasma levels of sICAM-1 and sVCAM-1 [70]. The same group subsequently conducted independent separate cross-sectional analyses and confirmed a positive association between lower arsenic exposure (median 23 μg/L, range 0.1–500.6 μg/L) and plasma levels of sVCAM-1 [71]. However, no significant association was observed for plasma levels of sE-selectin and sICAM-1.…”
Section: Markers Of Endothelial Dysfunction Inflammation and Oxidatmentioning
confidence: 97%
“…The Health Effects of Arsenic Longitudinal Study in Bangladesh (2007)(2008) has reported positive association between arsenic exposure from drinking water and plasma levels of markers of systemic inflammation and endothelial dysfunction. 124 In the same population, positive association has been found between inorganic arsenic exposure from drinking water and risk of hypertension , and more recently, increased cardiovascular mortality. Further basic, as well as, clinical research is needed to better define the role of arsenicosis in the aetiopathgenesis of CVD in Bangladeshi population.…”
Section: Chronic Arsenicosismentioning
confidence: 99%
“…For instance, chronic lead overload (both evaluated by its blood and bone levels) is associated to arterial hypertension and dyslipidemia [22]. As a result, an increase in vascular inflammation and endothelial damage markers [24] and early carotid atherosclerotic changes [25] have been reported in chronically exposed subjects to heavy metals. A possible role of air-released pollutants may also be supposed.…”
Section: Environmental Pollutants Tracingmentioning
confidence: 99%